Evaluation of fish behaviour and aggregation by underwater videography in an artificial reef in Tioman Island, Malaysia - T. Yoshida,; K. Akagi,; T . Toda,; M.M.R. Kushairi,; A.A.A. Kee,; B.H.R. Othman, (Universiti Kebangsaan Malaysia, 2010)
The behaviour and aggregation of fish in an artificial reef area in Tioman Island, Malaysia, was observed using underwater videography under a combination of shooting conditions. The camera distance and direction relative to the neighboring artificial reef module was varied, and comparisons of images with a color filter were made. A distance of 260 cm at a diagonal shooting angle provided a suitable observation of the reef fish around the reef module, and a red color filter provided a truer color replication in morning observations while better images were obtained without the color filter in afternoon light environments. Four criteria were considered to assess the artificial reef effectiveness: total abundance, appearance rate, residence time and feeding frequency. A total of 824 individuals were observed during the study. Mean residence times were shorter for schooling fishes such as Caesio caerulaurea and Liza subviridis, and longer for solitary swimmers like Cephalopholis boenak and Scolopsis bilineatus. Feeding frequency was lower for schooling fishes. A significant correlation was obtained between the feeding frequency and residence time for the high feeding frequency fishes (r = 0.89; p<0.05). The effectiveness of the artificial reef was suggested to be significant in solitary swimmers but less so for schooling fishes.